Pendampingan E-Commerce dan Pendidikan di Cerme Kecamatan Ngimbang Lamongan - Nasrullah, Dede; Hidayatullah, Achmad; Unggul WP, Satria (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2017)
Education and the economy are still a major problem in our country. The low level of community education causes the economy is still low. Cerme village of Lamongan regency is one example of civilization which also has problems both. This devotion focuses on the efforts to assist local msayarakt how to improve their reading ethos, internet recognize and how to do business or buying and selling transactions online or E-Commerce. Besides this dedication is done for one month. This form of advisory activities is the establishment of a reading park, internet installation and online business training or E-Commerce. With internet facilities that have been installed by UMSurabaya team hope after community training can access the latest knowledge and business with the help of internet. While for school children they can use the reading park and can access knowledge through the internet as well.